2014
DOI: 10.1007/s00535-014-0954-y
|View full text |Cite
|
Sign up to set email alerts
|

CTNNB1 mutational analysis of solid-pseudopapillary neoplasms of the pancreas using endoscopic ultrasound-guided fine-needle aspiration and next-generation deep sequencing

Abstract: Background: Solid-pseudopapillary neoplasm (SPN), a rare neoplasm of the pancreas,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…EUS-FNA demonstrates high sensitivity for histological diagnosis (75–94%) and a specificity approaching 100% in the majority of studies (5,6). However, false-negative, atypical and suspicious cytopathological diagnoses remain relatively frequent (5,7,8). …”
Section: Introductionmentioning
confidence: 99%
“…EUS-FNA demonstrates high sensitivity for histological diagnosis (75–94%) and a specificity approaching 100% in the majority of studies (5,6). However, false-negative, atypical and suspicious cytopathological diagnoses remain relatively frequent (5,7,8). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different NGS platforms use FNC to harvest cells from different tumors [92,93,94,95,96,97,98,99,100]. These studies demonstrated that NGS-based mutational profiling can be performed with a few nanograms of DNA (∼40 ng/μl), which can be easily obtained from FNC in different tumors [93,94,95,96,97,98]. Therefore, NGS may enhance the molecular FNC potential, providing mutational information on genes with high diagnostic and predictive relevance, such as EGFR, BRAF, K/N/HRAS, KIT, PTEN, CDKN2A, just to mention some, thus contributing to personalized therapies.…”
Section: High-throughput Technologies-based Arraysmentioning
confidence: 99%
“…There have been previous studies using next generation sequencing to analyze SPNs of the pancreas. However, in all these reports, the SPNs showed recurrent pathogenic variants only in the CTNNB1 gene …”
Section: Discussionmentioning
confidence: 93%